Gérez la procrastination et tirez le meilleur votre journée (Assemble You, 2022)
Welcome to Assemble You Audio Learning. In a 2000 survey, 88% of participants admitted to postponing at least one hour of work per day and 57.8% admitted to postponing at least two hours of work per day. If you want to make the most of your time, in order to be more productive and more successful than others, listen to the 5 tips in this ten-minute podcast. Learning objectives Learn 5 tips to fight procrastination and increase your productivity Learn to master your time and get the most out of your day.